The German ‘Appropriateness of Management Board Remuneration Act’: Impacts on German Executive and Supervisory Board Compensation – A Panel Data Approach - Ullrich, Tobias (2013)
With the enactment of the VorstAG on 5.8.2009 the stock corporation act was changed leading to increased risk and uncertainty for executives and elevated complexity, responsibility, and liability for directors. Hence, the present paper focuses on investigating the impact of the VorstAG on executive and director compensation and composition. Thereby, a DID approach was applied to analyse the dataset consisting of 29 German DAX30-listed companies and 10 AEX-listed Dutch firms, which severed as a control group. This research produced a number of key findings: firstly, executive total compensation, base salary, and long-term compensation components show insignificant results whilst short-term compensation decreased significantly after the enactment of the VorstAG. However, long-term executive compensation shows a positive trend. Thus, executive compensation schemes tend to be increasingly long-term oriented after the enactment of the VorstAG. Secondly, total director compensation also remains unaffected by the VorstAG. Nevertheless, base salary considerably increased and variable compensation components significantly decreased. Hence, director compensation is characterised by a rather risk-averse design after the enacting of the VorstAG. Accordingly, the main conclusion drawn from this research was that total executive and director compensation remains unaffected by the VorstAG. However, the executive compensation composition tends to develop into a more long-term aligned structure while director compensation shows a decreasing trend for uncertain variable compensation components and increasing fixed compensation elements leading to a more risk-averse structure. Consequently, the VorstAG seems to have the desired effect on executive compensation. However, the impact of the VorstAG on director compensation towards more fixed compen-sation elements might show a precarious trend.